Millimeter-sized spherical silica aerogel particles and methods for making the same

CN123002865APending Publication Date: 2026-10-30JIANGSU HANXIN TIANCHENG NEW MATERIAL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611330594.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0006]本申请旨在提供一种毫米级球形二氧化硅气凝胶颗粒及其制备方法,以解决现有技术中气凝胶颗粒形貌不规整、粒径控制不稳定、功能组分分散不均以及颗粒成型与干燥过程中易产生结构损伤等问题

Benefits of technology

1. 通过滴加成球与凝固浴原位凝胶相结合的方式,能够实现气凝胶颗粒的球形化制备,降低机械破碎方式带来的形貌不规则和骨架损伤问题;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123002865A_ABST
    Figure CN123002865A_ABST
Patent Text Reader

Abstract

The application discloses millimeter-sized spherical silica aerogel particles and a preparation method thereof. The preparation method comprises the steps of silica sol preparation, function deployment, coagulation bath configuration, gel and forming, and drying. First, silica sol is prepared, and functional fillers are added according to needs to uniformly disperse, forming doped silica sol. Then, the silica sol is delivered by constant current and added dropwise into a coagulation bath composed of ammonia and ethanol, so that sol droplets are in-situ gelled to form spherical wet gel particles. After ethanol replacement, supercritical ethanol drying is performed to obtain millimeter-sized spherical silica aerogel particles. The method can realize stable forming of particles and uniform deployment of functional materials. The obtained particles have the advantages of high sphericity, high porosity, low bulk density, good fluidity and strong application adaptability, and are suitable for scenes such as catalytic carrier, adsorption and pollution removal, building mortar, low-temperature storage and transportation, and filter filler.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of aerogel material preparation technology, and in particular to a millimeter-sized spherical silica aerogel particle and its preparation method. Background Technology

[0002] Silica aerogels possess advantages such as high porosity, low density, low thermal conductivity, and good heat resistance, making them promising for applications in thermal insulation, adsorption and purification, low-temperature storage and transportation, and functional filling. With the expansion of application scenarios, aerogel materials have gradually evolved from traditional forms such as blocks and sheets towards granular, spherical, and functional composite materials. Compared to irregular, fragmented aerogel particles, spherical particles typically exhibit better flowability, filling uniformity, and packing stability, making them more suitable for use as functional fillers, thermal insulation media, or composite material components.

[0003] Existing methods for preparing millimeter-sized aerogel particles mainly include integral wet gel crushing and sieving, spray granulation, and drop-forming. While integral wet gel crushing and sieving can produce granular products, the particle morphology is often irregular, with a wide particle size distribution. Furthermore, the mechanical crushing process can easily damage the aerogel skeleton, thus affecting the particle integrity, flowability, and subsequent performance. Spray granulation offers certain advantages in terms of continuity, but it requires high control over the viscosity, solid content, and drying process of the sol system, and still has limitations in obtaining particles with high sphericity, low density, and high porosity. While partial drop-forming processes can form near-spherical particles, there is still room for improvement in terms of spherical stability, particle size consistency, and subsequent drying shrinkage control.

[0004] Furthermore, existing aerogel particles are mostly based on a single silicon-based structure, and the introduction of functional components is relatively simple, often involving only coarse mixing at the sol stage. This makes it difficult to simultaneously ensure uniform dispersion of functional materials, particle molding stability, and the structural integrity of the final product. For specialized applications such as adsorption, catalysis, temperature resistance, and magnetic response, the uniform distribution of functional materials within the particles and their synergistic effect with the aerogel framework are particularly critical. Uneven dispersion of functional materials can easily lead to significant local structural differences within the particles, affecting the consistency of product performance and application reliability.

[0005] Therefore, there is an urgent need to provide a new millimeter-sized spherical silica aerogel particle and its preparation method to improve the problems of irregular particle morphology, insufficient particle size control precision, poor molding stability and uneven dispersion of functional materials in the existing technology, so as to obtain millimeter-sized spherical silica aerogel particles with high sphericity, stable pore structure, flexible functional formulation and suitable for mass production. Summary of the Invention

[0006] This application aims to provide millimeter-sized spherical silica aerogel particles and their preparation method, to solve the problems of irregular morphology, unstable particle size control, uneven dispersion of functional components, and structural damage during particle forming and drying in the prior art. By functionally adjusting the silica sol system and combining controlled droplet addition for spherical formation, in-situ gelation in a coagulation bath, and supercritical drying processes, stable preparation of millimeter-sized spherical aerogel particles is achieved, thereby improving the sphericity, flowability, pore structure integrity, and application adaptability of the particles.

[0007] To achieve the above objectives, this application adopts the following technical solution: A method for preparing millimeter-sized spherical silica aerogel particles, characterized by comprising the following steps: S1. Preparation of silica sol: A diluted solution of water glass and water is slowly added to a dilute sulfuric acid-ethanol solution to react until the pH of the reaction solution is 3.5-4.0. An equal volume of ethanol is added, and the precipitated sodium sulfate and gel are removed by filtration to obtain a water-alcohol silica sol filtrate. 0-15% of tetraethyl silicate is added to the filtrate and fully hydrolyzed to obtain silica sol. S2. Functional formulation: Add 0.1-5.0% of functional filler to the silica sol, and continuously disperse the functional filler evenly in the silica sol through mechanical dispersion to suppress the sedimentation of the functional filler before subsequent pelletizing, thereby obtaining a doped silica sol. S3. Coagulation bath preparation: Mix ammonia and ethanol at a mass ratio of (0.5-2.0):10 to form a coagulation layer with a depth of not less than 5 cm; add one or more of petroleum ether, n-hexane, or paraffin oil above the coagulation layer as a sealing layer with a depth of not less than 1 cm. S4. Gel and Formation: The silica sol or the doped silica sol is continuously delivered by a constant flow pump and added dropwise to the coagulation bath at a rate of 1-10 mL / min through multiple 9-30# needles. The distance between the needle and the liquid surface is 5-15 cm, so that the sol droplets gel in situ in the coagulation bath to form millimeter-sized spherical gel particles with a particle size of 1-4 mm. S5. Drying: After separating the millimeter-sized spherical gel particles from the coagulation bath, transfer them to a material tank containing ethanol and keep the particles submerged in ethanol. Then transfer them to a supercritical drying kettle for supercritical ethanol drying to obtain millimeter-sized spherical silica aerogel particles.

[0008] Preferably, the functional filler comprises one or more of carbon-based functional fillers, iron-based functional fillers, chromium-based functional fillers, lanthanide oxide functional fillers, and sodium-based functional fillers, so that the gel particles have at least one function of adsorption, catalysis, temperature resistance, modification, or molding regulation.

[0009] Preferably, in the functional preparation step S2, the silica sol is continuously dispersed by one or more of the following methods: mechanical stirring, cyclic shearing dispersion, and ultrasonic dispersion.

[0010] Preferably, the functional filler is dispersed in the silica aerogel framework and / or pores of the particles.

[0011] Preferably, the supercritical ethanol drying temperature in step S5 is 270℃~300℃, the pressure is 11~16MPa, and the discharge temperature is not higher than 150℃.

[0012] A millimeter-sized spherical silica aerogel particle, prepared according to any one of claims 1-5, is characterized in that the millimeter-sized spherical silica aerogel particle has a continuous spherical outer contour, a diameter of 0.5-3.0 mm, a sphericity of 1.0-1.3, a bulk density of 0.08-0.28 g / cm³, a porosity greater than 90%, a pore size of 10-30 nm, a pore volume of 0.5-3.0 cm³ / g, and a total immersion water absorption rate of less than 1%; furthermore, functional fillers are dispersed in the silica aerogel skeleton inside the particle, and the functional fillers are uniformly distributed inside the particle.

[0013] Preferably, the functional filler comprises one or more of the following: metal element filler, carbon-based filler, catalytic functional filler, adsorption functional filler, and heat-resistant functional filler, so that the particles have at least one of the functions of bearing, adsorption, catalysis, or enhancement.

[0014] Preferably, the functional filler is dispersed in the silica aerogel framework and / or pores of the particles.

[0015] Preferably, the particles are used in at least one of the following applications: catalyst carrier, adsorption and decontamination, building mortar, low-temperature storage and transportation materials, or filter media fillers.

[0016] Compared with the prior art, the present invention has at least the following beneficial effects: 1. By combining droplet addition for spherical formation with in-situ gelation in a coagulation bath, spherical preparation of aerogel particles can be achieved, reducing the problems of irregular morphology and skeleton damage caused by mechanical crushing. 2. Through the functional formulation step, functional materials can be uniformly introduced into the silica sol system before pelletizing, improving the dispersion uniformity of functional components and enhancing the consistency of particle performance; 3. The synergistic effect of the coagulation bath and the sealing layer can improve the stability of droplet formation, reduce adhesion, deformation and cracking, and improve particle sphericity and batch preparation stability; 4. Supercritical ethanol drying can preserve the particle pore structure to the maximum extent, resulting in aerogel particles with low density, high porosity, and low water absorption. 5. The millimeter-sized spherical silica aerogel particles prepared in this application have good flowability and filling properties, and can be used in a variety of applications such as catalyst carriers, adsorption and decontamination, building mortar, low-temperature storage and transportation, and filter media.

[0017] In summary, the millimeter-sized spherical silica aerogel particles and their preparation method provided in this application take into account particle morphology control, functional material formulation, and pore structure preservation, making them suitable for batch and stable preparation and possessing good application value. Attached Figure Description

[0018] Figure 1 This is a physical image of the aerogel particles corresponding to Embodiment 1 of the present invention; Figure 2 This is a photograph of the aerogel particles corresponding to the carbon-based functional filler in Example 2 of the present invention. Figure 3 This is a SEM image of the nanoporous structure of the aerogel particles in Example 2 of the present invention; Figure 4 The nitrogen adsorption-desorption curve and pore size distribution curve of the aerogel particles in Example 2 of the present invention are shown. Detailed Implementation

[0019] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.

[0020] The technical solution of the present invention will be described in detail below with reference to embodiments thereof. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Various modifications, equivalent substitutions, and improvements made by those skilled in the art without departing from the spirit of the present invention should fall within the scope of protection of the present invention.

[0021] Example 1 (Preparation of doped aerogel particles) S1. Preparation of silica sol: Water glass was diluted and added to a dilute sulfuric acid / ethanol mixture for reaction, and the pH of the system was adjusted to 3.9. After purification by ethanol filtration, 2.5% methyltriethoxysilane was added to the obtained silica sol. After complete hydrolysis, a highly hydrophobic silica sol was obtained.

[0022] S2. Functional Adjustment: In this embodiment, no additional functional fillers are introduced. The highly hydrophobic silica sol obtained in step S1 is directly used as the raw material for subsequent molding.

[0023] S3. Coagulation bath preparation: Mix ammonia water and ethanol at a mass ratio of 1.5:10 to form a coagulation layer with a depth of 5.5cm; lay a 1cm thick layer of paraffin oil on top of the coagulation layer as a sealing layer.

[0024] S4. Gel and Formation: Using a 30# needle, the highly hydrophobic silica sol is delivered at a rate of 3 mL / min using a constant flow pump. The height of the needle above the liquid surface is 10 cm, allowing the sol to enter the coagulation bath in the form of droplets and form small spherical gel particles.

[0025] S5. Drying: The obtained spherical gel particles were replaced with ethanol and then dried using supercritical ethanol at 285℃ and 14MPa to obtain highly hydrophobic pure silica aerogel particles. See the attached image for the aerogel particles corresponding to Example 1. Figure 1 .

[0026] Example 2 (Preparation of carbon-based functional spherical aerogel particles) S1. Preparation of silica sol: Water glass dilution solution is slowly added to a dilute sulfuric acid / ethanol mixed solution, and the pH of the system is controlled at 3.6 during the reaction. Then, an equal volume of ethanol is added and filtered to remove the precipitated sodium sulfate and impurity gel. Then, 10% tetraethyl silicate is added to the filtrate to adjust the silicon content and fully hydrolyze it to obtain silica sol.

[0027] S2. Functional formulation: Add 2% by mass of carbon-based functional filler to the silica sol obtained in step S1, and disperse it by high-speed stirring to ensure that the functional filler is uniformly distributed before spheroidization, thus obtaining doped silica sol.

[0028] Carbon-based functional fillers are used to enhance the adsorption performance, structural stability, or conductive properties of aerogel particles. Preferred materials include one or more of graphene, graphene oxide, carbon black, activated carbon, carbon nanotubes, carbon fibers, and mesoporous carbon. These fillers can serve as adsorption enhancement components or as composite framework enhancement components, enabling aerogel particles to maintain a lightweight, porous structure while improving their ability to capture organic molecules, gases, or pollutants.

[0029] S3. Preparation of coagulation bath: Mix ammonia water and ethanol at a mass ratio of 1.5:10 to form a coagulation layer with a depth of 5.5cm; lay a 1cm thick layer of paraffin oil on top of the coagulation layer as a sealing layer.

[0030] S4. Gel and Formation: Using a 15# needle, the constant flow pump is controlled at a flow rate of 3mL / min, and the height of the needle from the liquid surface is 8cm. The doped silica sol is dropped into the coagulation bath to form doped spherical gel particles in the coagulation bath.

[0031] S5. Drying: The obtained doped spherical aerogel particles were replaced with ethanol and then dried with supercritical ethanol at 290℃ and 14MPa. The discharge temperature was controlled at 135℃ to obtain carbon-doped millimeter-sized spherical aerogel particles.

[0032] Testing revealed that the particles had a diameter of 1.0–2.8 mm, a sphericity of 1.15, a bulk density of 0.18 g / cm³, a porosity of 92.5%, a pore size of 18–25 nm, and a total immersion water absorption rate of 0.55%. Images of the corresponding aerogel particles, SEM diagrams of the nanoporous structure, nitrogen adsorption-desorption curves, and pore size distribution curves for the carbon-based functional filler are attached. Figure 2-4 .

[0033] Example 3 (Preparation of iron-based functional spherical aerogel particles) S1. Preparation of silica sol: Industrial water glass was diluted with water and slowly added dropwise to a dilute sulfuric acid / ethanol mixed solution. The solution was stirred at a constant temperature to allow it to react fully, and the pH of the system was adjusted to 3.7. Then, an equal volume of anhydrous ethanol was added, and the solution was filtered to remove sodium sulfate crystals and trace impurities to obtain a clear water-alcohol silica sol. 5% tetraethyl silicate was added to the silica sol and hydrolyzed at room temperature for 3 hours to fine-tune the silicon content.

[0034] S2. Functional formulation: Add 1.5% by mass of iron-based functional filler to the silica sol obtained in step S1, and use mechanical stirring combined with ultrasonic dispersion for 30 minutes, while maintaining low-speed stirring to avoid sedimentation of the functional filler before subsequent sphere formation, to obtain a uniform iron-doped silica sol.

[0035] Iron-based functional packing materials are used to impart magnetic response, catalytic assistance, or oxidation reaction activity to particles, and are preferably one or more of iron oxide, magnetite, ferrohydride, ferrates, and iron powder. These packing materials can improve the catalytic activity of particles in specific reaction systems or facilitate subsequent separation and recovery via magnetic means.

[0036] S3. Coagulation bath preparation: Mix ammonia and ethanol at a mass ratio of 1.2:10 to form a coagulation layer with an effective depth of 5.5 cm; lay a 1.2 cm thick layer of n-hexane on top of the coagulation layer as a sealing layer.

[0037] S4. Gel and Formation: The iron-doped silica sol is continuously delivered using an 18# needle and a constant flow pump at a controlled flow rate of 4 mL / min. The needle is positioned 12 cm above the surface of the coagulation bath, allowing the sol to enter the coagulation bath in droplet form at a uniform speed and form spherical wet gel particles.

[0038] S5. Drying: After soaking and replacing the spherical wet gel particles with ethanol for 12 hours, the particles are transferred to a supercritical drying vessel and dried with supercritical ethanol at 285℃ and 12MPa. The discharge temperature is controlled below 140℃ to obtain iron-doped spherical aerogel particles.

[0039] The particles were found to have a diameter of 0.9–2.6 mm, a sphericity of 1.12, a bulk density of 0.16 g / cm³, and a porosity of 92.8%.

[0040] Example 4 (Chromium-based functional spherical aerogel particles) S1. Preparation of silica sol: Water glass dilution solution was slowly added to a dilute sulfuric acid / ethanol system, and the reaction was carried out under stirring. The pH value of the system was adjusted to 3.9. Then, an equal volume of ethanol was added for static purification, and impurities were removed by filtration to obtain pure silica sol. 1% by mass of methyltriethoxysilane was added to the silica sol for hydrophobic modification, and hydrolysis was carried out for 2.5 h.

[0041] S2. Functional adjustment: Add 3.0% by mass of chromium-based functional filler to the silica sol obtained in step S1, and stir continuously by mechanical dispersion to make the chromium-based functional filler evenly distributed in the silica sol and avoid agglomeration, so as to obtain chromium-doped modified silica sol.

[0042] Chromium-based functional fillers are mainly used to improve the temperature resistance, oxidation resistance, and high-temperature structural stability of particles. They are preferably one or more of chromium oxide, chromium-containing ceramic powder, chromite powder, and chromium nitrides. These fillers can synergistically enhance the thermal stability of the aerogel skeleton under high-temperature environments, reducing structural degradation of particles under thermal shock or high-temperature service conditions.

[0043] S3. Coagulation bath preparation: Mix ammonia and ethanol at a mass ratio of 1.8:10 to form a coagulation layer with a depth of 6cm; lay a 1cm thick petroleum ether layer on top of the coagulation layer as a sealing layer.

[0044] S4. Gel and Formation: The chromium-doped modified silica sol is delivered using a 22# needle and a constant flow pump at a controlled flow rate of 6 mL / min and a distance of 9 cm between the needle and the liquid surface. This allows the sol to be continuously added into the coagulation bath and gel in situ, forming spherical wet gel particles.

[0045] S5. Drying: After the obtained spherical wet gel particles are fully replaced with ethanol, they are placed in a supercritical drying kettle and dried with supercritical ethanol at 295℃ and 15MPa. The discharge temperature is controlled at 130℃ to obtain chromium-doped spherical aerogel particles.

[0046] The particles were tested and found to have a porosity of 93.2%, exhibiting good thermal stability and suitable for high-temperature insulation applications.

[0047] Example 5 (Lanthide oxide functional aerogel particles) S1. Preparation of silica sol: After the water glass dilution system is subjected to an acid-base reaction, the pH value of the system is adjusted to 3.6; then ethanol is added for filtration and purification, and 12% tetraethyl silicate is added to adjust the properties of the sol. After sufficient hydrolysis for 4 hours, silica sol is obtained.

[0048] S2. Functional adjustment: Add 1.0% by mass of lanthanide oxide functional filler to the silica sol obtained in step S1, and disperse it evenly in the silica sol by high-speed dispersion and stirring to reduce sedimentation and agglomeration, so as to obtain a high-adsorption performance doped silica sol.

[0049] Lanthanide oxide functional fillers are mainly used to enhance the adsorption, redox regulation, or high-temperature stability of particles, and are preferably one or more of cerium oxide, lanthanum oxide, praseodymium oxide, neodymium oxide, samarium oxide, and gadolinium oxide. These fillers can improve the surface activity and pore environment of materials, and are suitable for applications such as heavy metal adsorption, gas purification, or catalytic assistance.

[0050] S3. Coagulation bath preparation: Ammonia water and ethanol are mixed at a mass ratio of 0.8:10 to form a coagulation layer with a depth of 5cm; a 1.5cm thick layer of paraffin oil is laid on top of the coagulation layer as a sealing layer.

[0051] S4. Gel and Formation: Using a 12# needle, the flow rate is controlled at 2mL / min, and the height of the needle from the liquid surface is 11cm, so that the sol is dropped into the coagulation bath in a relatively stable droplet state and forms spherical gel particles.

[0052] S5. Drying: The obtained spherical gel particles were replaced with ethanol and then dried with supercritical ethanol at 275℃ and 11MPa. The discharge temperature was controlled at 145℃ to obtain lanthanide-doped spherical aerogel particles.

[0053] Testing revealed that the particle pore size is mainly distributed in the range of 12 to 20 nm, making it suitable for applications such as heavy metal adsorption and organic waste gas adsorption.

[0054] Example 6 (Sodium-based functional aerogel particles) S1. Preparation of silica sol: Silica sol is prepared by conventional water glass acid-base reaction, and the pH value of the system is adjusted to 3.8; then purified and filtered with ethanol to form basic silica sol. No additional silicon source or hydrophobic reagent is introduced in this embodiment.

[0055] S2. Functional Adjustment: Add 0.5% sodium-based functional filler by mass to the basic silica sol obtained in step S1, and disperse it by gentle stirring to improve the system stability and reduce the molding defect rate in the subsequent molding process, thereby obtaining sodium-doped silica sol.

[0056] Sodium-based functional fillers are mainly used to regulate the ionic environment, gel rate, and molding stability of silica sol systems. They are preferably one or more of sodium silicate, sodium aluminate, sodium carbonate, or sodium-containing inorganic powders. These fillers are more of a process control component, improving system stability during the drop-addition and pelletizing process, reducing gel defect rates, and thus improving particle uniformity.

[0057] S3. Coagulation bath preparation: Ammonia water and ethanol are mixed at a mass ratio of 1.0:10 to form a coagulation layer with a depth of 5cm; a 1cm thick layer of n-hexane is laid on top of the coagulation layer as a sealing layer.

[0058] S4. Gel and Formation: Using a 25# needle, the flow rate is controlled at 8 mL / min, and the height of the needle from the liquid surface is 6 cm. The sol is continuously added to the coagulation bath and rapidly formed to obtain spherical gel particles.

[0059] S5. Drying: The obtained spherical gel particles were replaced with ethanol and then dried with supercritical ethanol at 280℃ and 13MPa. The discharge temperature was controlled at 140℃ to obtain sodium-doped modified spherical aerogel particles.

[0060] Testing revealed that the granules have a high forming rate and good flowability, making them suitable for applications such as building mortar and conventional filter media filling.

[0061] In this invention, a mixed filler is formed by combining two or more of the above-mentioned functional fillers, such as a carbon-based and iron-based composite, a lanthanide oxide and carbon-based composite, or a chromium-based and sodium-based composite. This type of composite filler can simultaneously achieve multiple functions such as adsorption, catalysis, temperature resistance, and molding control within the same particle, thereby improving the overall performance and application adaptability of the particle.

[0062] In this invention, a coagulation bath is used to rapidly solidify and shape silica sol droplets added therein. Its function is to promote the formation of spherical wet gel particles from the sol droplets within a short time through alkaline triggering by the external environment, solvent exchange, and interfacial constraint. Preferably, the coagulation bath includes a coagulation layer and a sealing layer. The coagulation layer is formed by mixing ammonia and ethanol in a predetermined mass ratio. The ammonia provides alkaline conditions to promote a gelation reaction of the silica sol after the droplets enter. The ethanol adjusts the polarity and diffusion rate of the system and exchanges with the solvent in the droplets, thereby facilitating simultaneous solidification of the particle surface and interior, and preventing local collapse or cracking.

[0063] Preferably, the depth of the coagulation layer is not less than 5 cm to ensure sufficient settling and reaction space for the droplets after they enter, allowing them to complete preliminary gelation before contacting the bottom. Further, a sealing layer is provided above the coagulation layer. This sealing layer is preferably composed of one or more of petroleum ether, n-hexane, or paraffin oil. Its function is to reduce the evaporation rate of the coagulation bath surface, weaken the influence of air disturbance on the droplet trajectory and forming morphology, and prevent excessively rapid evaporation of ammonia and ethanol that could cause fluctuations in the gelation environment. The depth of the sealing layer is preferably not less than 1 cm to form a more stable surface coverage effect. Through the above coagulation bath configuration, the consistency and sphericity of particle forming can be improved, and the probability of particle adhesion, distortion, and breakage can be reduced.

[0064] In this invention, the gelation and molding steps are mainly used to transform silica sol into millimeter-sized spherical wet gel particles under controlled transport conditions. Preferably, the silica sol or doped silica sol is continuously transported to a needle via a constant flow pump and added dropwise from the needle to the coagulation bath at a set flow rate. By controlling the needle size, flow rate, and distance between the needle and the liquid surface, the sol can form relatively stable droplets upon leaving the needle. After entering the coagulation bath, the droplets undergo in-situ gelation under the combined action of gravity, surface tension, interfacial tension, and the alkaline environment of the coagulation bath, and gradually solidify into spherical wet gel particles.

[0065] Preferably, the needle size can be one of 9# to 30#, the flow rate can be 1-10 mL / min, and the distance between the needle and the liquid surface can be 5-15 cm. A larger needle size results in a relatively larger droplet diameter, suitable for preparing larger spherical particles; a smaller needle size results in a smaller droplet volume, suitable for preparing particles with finer dimensions and more uniform distribution. Furthermore, simultaneous addition using multiple needles can improve batch production efficiency while ensuring particle shape consistency. The droplets preferentially form a near-spherical shape in the coagulation bath, and then remain in a wet gel state after the gelation reaction is complete. Separation, displacement, and drying then yield the final aerogel particles. This forming method effectively avoids the problems of irregular particle shape, wide particle size distribution, and severe skeleton damage in traditional crushing and granulation, thereby improving particle regularity, flowability, and adaptability for subsequent applications.

[0066] Compared with the prior art, this application has the following beneficial effects: 1. By combining droplet addition for spherical formation with in-situ gelation in a coagulation bath, spherical preparation of aerogel particles can be achieved, reducing the problems of irregular morphology and skeleton damage caused by mechanical crushing. 2. Through the functional formulation step, functional materials can be uniformly introduced into the silica sol system before pelletizing, improving the dispersion uniformity of functional components and enhancing the consistency of particle performance; 3. The synergistic effect of the coagulation bath and the sealing layer can improve the stability of droplet formation, reduce adhesion, deformation and cracking, and improve particle sphericity and batch preparation stability; 4. Supercritical ethanol drying can preserve the particle pore structure to the maximum extent, resulting in aerogel particles with low density, high porosity, and low water absorption. 5. The millimeter-sized spherical silica aerogel particles prepared in this application have good flowability and filling properties, and can be used in a variety of applications such as catalyst carriers, adsorption and decontamination, building mortar, low-temperature storage and transportation, and filter media.

[0067] In summary, the millimeter-sized spherical silica aerogel particles and their preparation method provided in this application take into account particle morphology control, functional material formulation, and pore structure preservation, making them suitable for batch and stable preparation and possessing good application value.

Claims

1. A method for preparing millimeter-sized spherical silica aerogel particles, characterized in that, Includes the following steps: S1. Preparation of silica sol: A diluted solution of water glass and water is slowly added to a dilute sulfuric acid-ethanol solution to react until the pH of the reaction solution is 3.5-4.

0. An equal volume of ethanol is added, and the precipitated sodium sulfate and gel are removed by filtration to obtain a water-alcohol silica sol filtrate. 0-15% of tetraethyl silicate is added to the filtrate and fully hydrolyzed to obtain silica sol. S2. Functional formulation: Add 0.1-5.0% of functional filler to the silica sol, and continuously disperse the functional filler evenly in the silica sol through mechanical dispersion to suppress the sedimentation of the functional filler before subsequent pelletizing, thereby obtaining a doped silica sol. S3. Coagulation bath preparation: Mix ammonia and ethanol at a mass ratio of (0.5-2.0):10 to form a coagulation layer with a depth of not less than 5 cm; add one or more of petroleum ether, n-hexane, or paraffin oil above the coagulation layer as a sealing layer with a depth of not less than 1 cm. S4. Gel and Formation: The silica sol or the doped silica sol is continuously delivered by a constant flow pump and added dropwise to the coagulation bath at a rate of 1-10 mL / min through multiple 9-30# needles. The distance between the needle and the liquid surface is 5-15 cm, so that the sol droplets gel in situ in the coagulation bath to form millimeter-sized spherical gel particles with a particle size of 1-4 mm. S5. Drying: After separating the millimeter-sized spherical gel particles from the coagulation bath, transfer them to a material tank containing ethanol and keep the particles submerged in ethanol. Then transfer them to a supercritical drying kettle for supercritical ethanol drying to obtain millimeter-sized spherical silica aerogel particles.

2. The preparation method according to claim 1, characterized in that, The functional filler includes one or more of carbon-based functional fillers, iron-based functional fillers, chromium-based functional fillers, lanthanide oxide functional fillers, and sodium-based functional fillers, so that the gel particles have at least one function of adsorption, catalysis, temperature resistance, modification, or molding regulation.

3. The preparation method according to claim 1, characterized in that, In the functional preparation step S2, the silica sol is continuously dispersed by one or more of the following methods: mechanical stirring, cyclic shearing dispersion, and ultrasonic dispersion.

4. The preparation method according to claim 3, characterized in that, The functional filler is dispersed in the silica aerogel framework and / or channels of the particles.

5. The preparation method according to claim 1, characterized in that, The supercritical ethanol drying temperature in step S5 is 270℃~300℃, the pressure is 11~16MPa, and the discharge temperature is not higher than 150℃.

6. A millimeter-sized spherical silica aerogel particle, prepared by the method according to any one of claims 1-6, characterized in that, The millimeter-sized spherical silica aerogel particles have a continuous spherical outer contour, a diameter of 0.5–3.0 mm, a sphericity of 1.0–1.3, a bulk density of 0.08–0.28 g / cm³, a porosity greater than 90%, a pore size of 10–30 nm, a pore volume of 0.5–3.0 cm³ / g, and a total immersion water absorption rate of less than 1%. Furthermore, functional fillers are dispersed in the silica aerogel skeleton inside the particles, and the functional fillers are uniformly distributed inside the particles.

7. The millimeter-sized spherical silica aerogel particles according to claim 6, characterized in that, The functional filler includes one or more of the following: metal element filler, carbon-based filler, catalytic functional filler, adsorption functional filler, and heat-resistant functional filler, so that the particles have at least one of the functions of carrying, adsorption, catalysis, or enhancement.

8. The millimeter-sized spherical silica aerogel particles according to claim 6, characterized in that, The functional filler is dispersed in the silica aerogel framework and / or channels of the particles.

9. The millimeter-sized spherical silica aerogel particles according to any one of claims 6 to 8, characterized in that, The particles are used in at least one of the following applications: catalyst carrier, adsorption and decontamination, building mortar, low-temperature storage and transportation materials, or filter media.